Ruptura do ligamento cruzado cranial em gatos: estudo retrospectivo - Freitas, Laura Lourenço (2021)
Rupture of the cranial cruciate ligament (CrCL) is a condition still poorly clarified in cats. It is believed that there are two distinct groups in the feline species that can manifest an injury to the CrCL: in the first group, the rupture of the CrCL is associated to the evident traumatic factor; in the second group, the CrCL injury is associated with degenerative factors. This study aimed to evaluate several characteristics of cats with ruptured CrCL to elucidate the condition in this species. A retrospective study of 26 cats with clinical rupture of the CrCL was carried out, which were categorized into two main groups, taking into account the type of lesion present (G1 and G2). The G1 group consisted of cats that presented the CrCL rupture as an injury associated with evident traumatic injuries in the knee joint, and the G2 group consisted of cats that presented the CrCL rupture as an injury alone or in association with an alteration in meniscus. From this division, analysis and verification of the statistical association of G1 and G2 for the following variables was performed: life stage, body score, indoor/outdoor behavior, degree of lameness, type of trauma and signs of joint degeneration. In the radiographs, measurements of the tibial plateau angle (TPA) were performed, and signs of joint degeneration were evaluated, when present, in a double-blind study. Histological samples of knee joint structures were obtained from four cats with CrCL rupture belonging to the two groups (G1 and G2). For statistical analysis, contingency tables were created, and association test using nominal qualitative variables, Chi-Square Partition Test and Fisher's Exact Test were performed. A significant association (p<0.05) was observed between cats with indoor behavior, non-existent or mild traumatic history and the presence of radiographic signs of joint degeneration with the group that presented isolated rupture of the CrCL (G2). The measurement of the TPA indicated that the rupture of the CrCL does not seem to be influenced by the inclination of the tibial plateau in cats. In the histopathological evaluation, characteristics suggestive of a degenerative joint process were observed. It is concluded that degenerative changes may be related to the etiology of CrCL rupture in cats.